Senator Roland E. Kannenberg - Hoeppner, Gail (My University, 1972)
This study was done for Wisconsin History. I chose the former State Senator Roland E. Kannenberg because I was interested in the Progressive Movement, which Mr. Kannenberg was part of, and his career sounded very interesting. This is a biography of the former Senator with greatest emphasis on his time in politics. I would like to extend my appreciation to Senator Roland E. Kannenberg, Mayor John Kannenberg (brother), Natalie (Kannenberg) Tackett (daughter), and Walter A. Graunke, without whom this paper could not have been written.
Keywords: Kannenberg, Roland E.; Legislators--Wisconsin; Progressivism (United States politics)--History; Progressive Party of Wisconsin